Labov in sociolinguistics: An introduction. (23rd September 2016) - Bell, Allan; Sharma, Devyani; Britain, David
Abstract : This theme issue marks fifty years since the publication of William Labov's Social Stratification of English in New York City, the foundation study of variationist sociolinguistics. This Introduction offers the editors' rationale for the shape of the issue. We briefly survey the innovations and impact of the New York study, together with the subsequent development of the field by Labov and others. We then touch on several strands of Labov's contribution to sociolinguistics: language change, linguistic evaluation, methodological innovation, African American English, language and the individual, and language style. We conclude with a reflection on Labov's commitment to the study of language in society.